Underwater Photo-Elicitation: A New Experiential Marine Education Technique. (23rd April 2018) - Andrews, Steve; Stocker, Laura; Oechel, Walter
Abstract: Underwater photo-elicitation is a novel experiential marine education technique that combines direct experience in the marine environment with the use of digital underwater cameras. A program called Show Us Your Ocean! (SUYO!) was created, utilising a mixed methodology (qualitative and quantitative methods) to test the efficacy of this technique. Participants (adults and high school students) snorkelled, explored the ocean, and captured images both in and out of the water. Underwater photo-elicitation was proven effective at increasing awareness, eliciting emotional reactions, and fostering a sense of connection to the ocean. However, it was not necessarily effective for raising awareness of environmental issues nor for motivating pro-environmental behaviour. Interestingly, while some attitudes about and behaviours toward the ocean did become more environmentally sensitive, others appeared to shift unexpectedly away from environmental concern. This result was perhaps due to the lack in the program of an ecological knowledge-based component. Participants enjoying the beauty of the ocean did not realise the threats facing it or what to do about these. If the goal is to achieve significant attitude change and cultivate pro-environmental behaviour, this new approach should be supplemented with critical thinking/action competence and ecological/ocean literacy.